PROGRAM EDUKASI ANEMIA UNTUK SISWA SMP: “KENALI ANEMIA, JAGA SEHATMU!” - Srikandi, Uci Meutia; Yolanda, Tanaya; Rahmadani, Zahra Dwita Putri; Simanungkalit, Nur Aysah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Anemia is a common health issue among adolescents, primarily caused by iron deficiency. This condition can negatively impact students' academic performance, physical growth, and psychological well-being. The program